Determinants and impacts of risk disclosure quality: evidence from China. Issue 4 (12th November 2018) - Elshandidy, Tamer; Neri, Lorenzo; Guo, Yingxi
Abstract : Purpose: Few studies have focused on emerging markets owing to difficulties in identifying the real effect of disclosures on these economies. To fill this gap, the purpose of this paper is to first: investigate the main drivers for risk disclosure quality for Chinese financial firms, second: further study the impact of such disclosure on market liquidity. Design/methodology/approach: The sample comprises all financial firms listed in the Shanghai A-shares market for the period 2013–2015. By relying on manual content analysis of annual reports, the risk disclosure quality is measured through a multidimensional approach which encompasses three factors: quantity of disclosure, coverage of disclosure and the semantic properties of depth and outlook. The findings of this paper are based on ordinary least squares and fixed-effects estimations. Findings: The findings suggest that firm characteristics (especially size) influence risk disclosure practices of Chinese financial companies. Furthermore, the authors found that risk disclosure quality has an impact on market liquidity, and when the authors analysed each year the authors noticed that the results were driven by the year 2013; moreover, the authors noticed no or little significance from the period of the emerging financial crisis. Research limitations/implications: The sample of this paper is limited to financial firms in China. The usage of manual content analysis limits the authors' ability to investigate risk reporting drivers and its impact on market liquidity on a large scale. Practical implications: The importance of this paper stems from documenting several reporting incentives concerning not only firms' quantity, but also firms' quality of risk reporting. Collectively, the findings support activism for reforms and the enhancement of regulations in China in order to make the market more efficient. Originality/value: This paper provides new evidence for financial companies in China on the principal drivers for risk disclosure quality and highlights how the quality of such disclosure impacts market liquidity. Furthermore, this paper confirms previous findings on the Chinese market (Ball et al., 2000 ;Zou and Adams, 2008 ) in which, given a decreasing but still strong state presence, there is higher stock volatility and weak corporate governance.